Pengolahan snack ikan patin sebagai cemilan sehat di Kelurahan Rumbai Bukit Kecamatan Rumbai Kota Pekanbaru - N Ira Sari; Dian Iriani; Bustari Hasan; Tjipto Leksono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
This catfish is a fish that is being cultivated in Pokdakan, Rumbai Bukit village, Rumbai DIstrict, Pekanbaru City, with production of 3-6 tons per harvest. To overcome the abundance of production and extend the shelf life, a diversified processing of fishery products is carried out in making snacks. The purpose of this community service is to provide the ability and practical skills to the community of Rumbai Bukit Village Pekanbaru in making snacks of various flavors of catfish with high nutritional value so that they can increase fish protein consumption for family members and are expected to develop it in the form of a household industry or small industry groups in this area so that it can help the family economy. The method used is a method of survey, interview, observation, lecture, discussion and training on processing fish snacks. The results obtained were that the community of Rumbai Bukit Village was very enthusiastic in participating in this training activity. Based on the post test, 95% of the community has been able to make processed fish products in the form of fish snacks both individually and in groups, knowing the product packaging and labeling techniques.